Successful treatment of a severe course of coronavirus infection in the obese polymorbid patient after bariatric surgery - I. P. Siutkina; D. V. Khabarov; P. V. Bulychev; A. Yu. Demura; A. D. Inyoshina (Бюллетень сибирской медицины)
We presented a clinical case of the successful treatment of a severe course of polysegmental pneumonia caused by the novel coronavirus infection, that developed in the postoperative period after bariatric surgery in the patient with morbid obesity, comorbid type 2 diabetes mellitus, ischemic heart disease, arterial hypertension, pulmonary embolism (in past medical history), and stage 3 chronic obstructive pulmonary disease. The given clinical case demonstrates the possibility of successful treatment of coronavirus infection in the polymorbid patient at an extremely high risk of an unfavorable outcome, given timely diagnosis, combination therapy using drugs that block cytokine storm, and strict adherence to clinical recommendations.